FUTURE PILOTS PROFESSIONAL ADAPTATION IN FLIGHT HIGHER SCHOOL AS A SUBJECT OF SCIENTIFIC RESEARCH - Бродова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article presents an analysis of the basic scientific approaches into defining the essence and content of the concept of «professional adaptation». Consider professional, social, psychological and psychophysiological approaches to the study of adaptation. The author described the future pilot’s professional adaptation in flight higher school